2009
DOI: 10.1029/2009rs004201
|View full text |Cite
|
Sign up to set email alerts
|

Ultrawideband pulse propagation through a homogeneous, isotropic, lossy plasma

Abstract: [1] We investigate a linearly polarized, plane wave electromagnetic step function modulated sine wave pulse traveling through an isotropic, homogeneous, lossy plasma with dielectric permittivity described by the Drude model. The results of this investigation extend the useful frequency domain below the plasma cutoff frequency. An asymptotic method of analysis is used to provide a closed-form approximation to the integral representation of the propagated pulse that is valid for all input carrier frequencies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…When an ultrawide-band pulse propagates through plasma, the attenuation factor C of the Brillouin precursor is -2. However, the other precursor (Sommerfeld precursor) can have a smaller attenuation factor of -0.75 [8]. High frequencies give rise to the Sommerfeld precursor, while low frequencies give rise to the Brillouin precursor.…”
Section: B Peak Amplitude Attenuation Through Sea Water Using a Doubmentioning
confidence: 97%
See 1 more Smart Citation
“…When an ultrawide-band pulse propagates through plasma, the attenuation factor C of the Brillouin precursor is -2. However, the other precursor (Sommerfeld precursor) can have a smaller attenuation factor of -0.75 [8]. High frequencies give rise to the Sommerfeld precursor, while low frequencies give rise to the Brillouin precursor.…”
Section: B Peak Amplitude Attenuation Through Sea Water Using a Doubmentioning
confidence: 97%
“…Each spectral component travels through the medium with its own phase velocity and attenuation rate, so that the phase relationship and the relative amplitudes between the spectral components of the pulse change with propagation distance. Asymptotic theory can accurately describe this complex dynamic evolution of the propagation field [5]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…We restrict our analysis to the branch on which Re[k(ω)] is negative by introducing one branch cut that extends between the branch points −iδ + 1 −δ 2 and − iδ + 1 +ω 2 p −δ 2 (6) in the right half plane and another branch cut symmetrically located across the imaginary axis.…”
Section: Formulationmentioning
confidence: 99%
“…It wasn't until the late 1970's that the results of Oughstun and Sherman [3] clearly showed that the peak amplitude point of the Brillouin precursor occurs at the space-time point ct/z = (0) and that the field at this spacetime point decays algebraically with propagation distance, whereas the remainder of the field decays exponentially. Since then, asymptotic methods have been used successfully to describe the propagation of step-modulated sinusoids of fixed central frequency through single-resonance Lorentz material [4], Rocard-Powles-Debye material [5] and lossy plasma [6], as well as propagation of a Gaussianmodulated cosine wave of fixed central frequency through a single-resonance Lorentz dielectric [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The asymptotic description with the integral representation of the propagated plane-wave pulse was used in the study. The same technique was used to study the propagation of the step sinusoidal wave (Cartwright & Oughstun 2009). Although the obtained result was valid for all input carrier frequencies, special attention was paid to the carrier frequency below the plasma frequency.…”
Section: Introductionmentioning
confidence: 99%